Breastfeeding media coverage and beliefs during the COVID-19 pandemic in Mexico: implications for breastfeeding equity - M. Vilar-Compte; P. Gaitán-Rossi; E. C. Rhodes; V. Cruz-Villalba; R. Pérez-Escamilla (BMC, 2021)
Abstract Background Because breastfeeding offers short- and long- term health benefits to mothers and children, breastfeeding promotion and support is a public health priority. Evidence shows that SARS-CoV-2 is not likely to be transmitted via breastmilk. Moreover, antibodies against SARS-CoV-2 are thought to be contained in breastmilk of mothers with history of COVID-19 infection or vaccination. WHO recommends direct breastfeeding as the preferred infant feeding option during the COVID-19 pandemic, even among women with COVID-19; but conflicting practices have been adopted, which could widen existing inequities in breastfeeding. This study aims to describe how information about breastfeeding was communicated in Mexican media during the pandemic and assess Mexican adults' beliefs regarding breastfeeding among mothers infected with COVID-19. Methods We conducted a retrospective content analysis of media coverage on breastfeeding in Mexico between March 1 and September 24, 2020, excluding advertisements. For the content analysis, we performed both a sentiment analysis and an analysis based on strengths, weaknesses, opportunities, and threats (SWOT) for breastfeeding promotion. Additionally, we conducted a descriptive analysis of nationally representative data on adults' beliefs about breastfeeding from the July 2020 round of the ENCOVID-19 survey in Mexico and stratified the results by gender, age, and socioeconomic status. Results A total of 1014 publications on breastfeeding were identified on the internet and television and in newspapers and magazines. Most information was published during World Breastfeeding Week, celebrated in August. The sentiment analysis showed that 57.2% of all information was classified as positive. The SWOT analysis indicated that most information focused on current actions, messages, policies, or programs that enable breastfeeding (i.e., strengths) or those not currently in place but that may enable breastfeeding (i.e., opportunities) for breastfeeding promotion. However, ENCOVID-19 survey results showed that 67.3% of adults living in households with children under 3 years of age believe that mothers with COVID-19 should not breastfeed, and 19.8% do not know whether these mothers should breastfeed. These beliefs showed differences both by gender and by socioeconomic status. Conclusions While the Mexican government endorsed the recommendation on breastfeeding during the COVID-19 pandemic, communication was sporadic, inconstant and unequal across types of media. There was a widespread notion that mothers with COVID-19 should not breastfeed and due to differences on beliefs by socioeconomic status, health inequities could be exacerbated by increasing the risk of poorer breastfeeding practices and preventing vulnerable groups from reaping the short and long-term benefits of breastfeeding.